A companion to film noir - Spicer, Andrew, 1953-; Hanson, Helen (Wiley Blackwell, 2013)
"An authoritative companion that offers a wide-ranging thematic survey of this enduringly popular cultural form and includes scholarship from both established and emerging scholars as well as analysis of film noir's influence on other media including television and graphic novels. Covers a wealth of new approaches to film noir and neo-noir that explore issues ranging from conceptualization to cross-media influences Features chapters exploring the wider 'noir mediascape' of television, graphic novels and radio Reflects the historical and geographical reach of film noir, from the 1920s to the present and in a variety of national cinemas Includes contributions from both established and emerging scholars "--